PENGARUH PROFITABILITAS DAN KEPEMILIKAN PUBLIK TERHADAP KETEPATAN WAKTU PENYAMPAIAN LAPORAN KEUANGAN - Andriana, Denny; Arina Raspati, Nada (Jurnal Riset Akuntansi dan Keuangan, 2015)
This study aims to determine the effect of profitability and public ownership on the timeliness of financial reporting. Determination of the sample using purposive sampling method with total samples obtained as many as 363 companies listed on the Indonesia Stock Exchange for the period 2011 to 2013. Data analysis techniques used in this study is logistic regression. The test results show that profitability significantly influence the timeliness of financial statement submission. While public ownership has no significant influence on the timeliness of financial statement submission.